2018
DOI: 10.4314/sajas.v48i3.2
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and postpartum effects of starch and fat in dairy cows: A review

Abstract: This review discusses the effects of starch and fat before and after calving on metabolism, energy balance (EB), milk production, and reproduction in dairy cows. The shift in dairy cows from a pregnant nonlactating state to a non-pregnant lactating state induces physiological changes, which affect the metabolic and endocrinal axes to redirect body energy stores towards the mammary gland for milk production. Overfeeding high starch and fat levels during the dry period after calving may result in cows failing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 133 publications
(284 reference statements)
0
5
0
Order By: Relevance
“…Therefore, cows, like other lactating animals, often enter a negative energy balance (NEB) at the start of lactation [ 83 ], approximately during the initial 30 days [ 84 ], or even up to 70 to 84 days postpartum (pp) [ 85 ]. Mammary function has metabolic priority and thus, in the NEB state, the limited available nutrients in an organism are directed to milk synthesis for survival of offspring [ 86 ]. Body reserves (fat, and to a lesser degree, protein) are mobilized [ 87 ] through homeostatic regulation [ 85 , 88 ].…”
Section: Effects Of Nutrition and Metabolic Aspects Of Cattle On Mmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, cows, like other lactating animals, often enter a negative energy balance (NEB) at the start of lactation [ 83 ], approximately during the initial 30 days [ 84 ], or even up to 70 to 84 days postpartum (pp) [ 85 ]. Mammary function has metabolic priority and thus, in the NEB state, the limited available nutrients in an organism are directed to milk synthesis for survival of offspring [ 86 ]. Body reserves (fat, and to a lesser degree, protein) are mobilized [ 87 ] through homeostatic regulation [ 85 , 88 ].…”
Section: Effects Of Nutrition and Metabolic Aspects Of Cattle On Mmentioning
confidence: 99%
“…Consequently, non-esterified FAs (NEFAs) are released from body fat reserves, with increasing NEFA levels in blood suggesting a shortfall in energy balance [ 92 ]. NEFA metabolites are directed into the mammary gland to supply milk triglycerides or utilized in the liver [ 86 , 93 , 94 , 95 ].…”
Section: Effects Of Nutrition and Metabolic Aspects Of Cattle On Mmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that a glucogenic diet could stimulate the ovary to utilize glucose, improving somatotropic axis synergies with the gonadotropins (FSH, LH, and P4, etc.) in post-partum dairy cows 28 .…”
Section: Discussionmentioning
confidence: 99%
“…This result agreed with Hess et al (2019) who reported that the grain component of the basal diet did not affect milk yield of dietary fat supplements. Admittance levels and types of dietary energy sources, such as starch and fat, affected plasma metabolite profiles, milk production, and fertility of dairy cattle (Useni et al, 2018). In addition, feeding fats have a positive effect on fertility and a tendency to increase production when fed during the transition period (Rodney et al, 2015).…”
Section: Feed Consumptionmentioning
confidence: 99%